Peningkatan Penguasaan Kosakata Bahasa Arab Siswa Melalui Penggunaan Aplikasi Kahoot - Alfan Aulawi (Journal of Arabic Education and Linguistic, 2024)
Mastery of Arabic vocabulary is a fundamental component in language learning. Vocabulary is the main element for understanding and expressing meaning in oral and written communication. This research aims to improve students' mastery of Arabic vocabulary through implementing the Kahoot application at SMP Plus Intan as-Sali. The type of research used in this research is experimental research with a one group pretest posttest design. The data collection technique used is in the form of a test. The research results showed that there were differences in learning outcomes before and after being given treatment, namely the pretest score was 77.08 to 92.46 on the posttest. The results of hypothesis testing using the paired sample test show that the sig value (2 tailed) is as large 0,004 as the sig value <0.05. So it can be concluded that the Kahoot application has an influence on the Arabic vocabulary mastery of class VII SMP Plus Intan as-Sali students.